(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify: the effect of the Pentagram strategy on the collection of design techniques for students of the Department of Art Education, and to verify this, the following hypothesis was formulated: There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group, which are taught according to the Pentagram strategy, and the mean scores of the students of the control group, which are taught according to the usual method, in the achievement test of Design Techniques The research community was determined by the students of the third stage / Department of Art Education - Morning Study / College of Basic Education at Al-Mustansiriya University. The researcher selected the study material that will be taught during the duration of the experiment, which is six topics from the Design Techniques subject, formulated (60) behavioral goals, and prepared daily plans for teaching the two research groups. The researcher prepared a test My cognitive achievement consisted of (35) test items and the design of a questionnaire to evaluate the skillful performance, and the researcher made sure of its validity and stability. After analyzing the results statistically, the researcher concluded that the experimental group that studied the subject of design techniques using the Pentagram strategy in the cognitive and skill posttest outperformed the control group that studied the same subject on According to.